Students' perceptions of native and non-native English-speaking teachers and their influence on students' motivation - El-Sawah, Sarah Ossama (AUC Knowledge Fountain, 2020)
The present study aims to investigate students' perceptions of native English-speaking teachers (NEST) and non-native English-speaking teachers (NNEST) and the techniques used by both types of teachers to influence students' motivation. Both qualitative and quantitative research methods were employed to answer the research questions. A sample of 82 Egyptian learners enrolled in the Intensive English Program (IEP) at the American University in Cairo (AUC) and a sample of two native IEP teachers and two non-native IEP teachers participated in the study. A questionnaire was sent to students to identify students' perceptions of the instructional practices and motivational techniques utilized by both NESTs and NNESTs. A classroom observation scheme was also used to document the minute-by-minute motivational techniques used by teachers. Triangulating the results, the investigator conducted semi-structured interviews for further in-depth analysis of the research questions. The results showed that students hold more positive perceptions towards the instructional practices and motivational techniques used by the non-native English-speaking teacher. The findings also revealed that the motivational techniques used by both types of teachers in the teaching process varied.